Laminar Free and Forced magnetoconvection through an Octagonal Channel with a Heat Generating Circular Cylinder - Nasrin, Rehena; Alim, MA (Journal of Naval Architecture and Marine Engineering, 2012)
In this paper, hydromagnetic flow and thermal behaviors of fluid on free and forced convection inside an octagonal vertical channel are investigated. The channel consists of a centered heat generating hollow solid circular cylinder. The vertical and inclined walls of the octagon are insulated perfectly. The input and output opening are situated at the bottom and top surface respectively. The octagon is filled with electrically conducting fluid. The integral forms of the governing equations are solved numerically using Galerkins Weighted Residual Finite Element method. Computational domains are divided into finite numbers of body fitted control volumes with collocated variable arrangement. Results are presented in the form of average Nusselt number (Nu) and maximum temperature (?max) of the fluid for a selected range of magnetic parameter Hartmann number Ha (0 - 50). Streamlines and isothermal lines are also displayed for three different values (0.1, 1 and 10) of convection parameter (Ri) and for a fluid having magnetic field. The results indicate that the highest Nu and ?max are found for the absence of Ha in all convection regions. DOI: http://dx.doi.org/10.3329/jname.v9i1.7891 Journal of Naval Architecture and Marine Engineering 9(2012) 25-34